Quantum-mechanical simulations for in vivo MR spectroscopy: Principles and possibilities demonstrated with the program NMRScopeB - Starčuk, Zenon; Starčuková, Jana (Analytical biochemistry, 2017)
Current possibilities and limitations of the simulation of in vivo magnetic resonance spectroscopic signals are demonstrated from the point of view of a simulation software user as well as its programmer. A brief review of the quantum-mechanical background addresses the specific needs of simulation implementation and in vivo MR spectroscopy in general. Practical application examples demonstrate how flexible simulation software, such as NMRScopeB, can be utilized not only for the preparation of metabolite basis signals for quantification of metabolite concentrations, but also in pulse sequence development, assessment of artifacts and analyzing mechanism leading to unexpected signal phenomena.
Keywords: In vivo spectroscopy; magnetická rezonanční tomografie; Computer Simulation; magnetická rezonanční spektroskopie; kvantová teorie; Magnetic Resonance Spectroscopy; Metabolite concentration quantitation; Software; Models, Biological; Magnetic resonance spectroscopy; Animals; lidé; biologické modely; Humans; zvířata; počítačová simulace; Quantum Theory; software; Magnetic Resonance Imaging; Quantum mechanical simulation